The SOMATICS collaborative: Introduction to a National Institute on Drug Abuse cooperative study of pharmacotherapy for opioid treatment in criminal justice settings - Chandler, Redonna K. (Contemp Clin Trials, 2016)
BACKGROUND: Among the nearly 750,000 inmates in U.S. jails, 12% report using opioids regularly, 8% report use in the month prior to their offense, and 4% report use at the time of their offense. Although ample evidence exists that medications effectively treat Opiate Use Disorder (OUD) in the community, strong evidence is lacking in jail settings. The general lack of medications for OUD in jail settings may place persons suffering from OUD at high risk for relapse to drug use and overdose following release from jail. METHODS: The three study sites in this collaborative are pooling data for secondary analyses from three open-label randomized effectiveness trials comparing: (1) the initiation of extended-release naltrexone [XR-NTX] in Sites 1 and 2 and interim methadone in Site 3 with enhanced treatment-as usual (ETAU); (2) the additional benefit of patient navigation plus medications at Sites 2 and 3 vs. medication alone vs. ETAU. Participants are adults with OUD incarcerated in jail and transitioning to the community. RESULTS: We describe the rationale, specific aims, and designs of three separate studies harmonized to enhance their scientific yield to investigate how to best prevent jail inmates from relapsing to opioid use and associated problems as they transition back to the community. CONCLUSIONS: Conducting drug abuse research during incarceration is challenging and study designs with data harmonization across different sites can increase the potential value of research to develop effective treatments for individuals in jail with OUD.